Factor Xa Activation of Factor V Is of Paramount Importance in Initiating the Coagulation System: Lessons From a Tick Salivary Protein - Schuijt, Tim J.; Bakhtiari, Kamran; Daffre, Sirlei; DePonte, Kathleen; Wielders, Simone J.H.; Marquart, J. Arnoud; Hovius, Joppe W.; van der Poll, Tom; Fikrig, Erol; Bunce, Matthew W.; Camire, Rodney M.; Nicolaes, Gerry A.F.; et al. (Circulation (New York, N.Y.), 2013)
BACKGROUND—Generation of active procoagulant cofactor factor Va (FVa) and its subsequent association with the enzyme activated factor X (FXa) to form the prothrombinase complex is a pivotal initial event in blood coagulation and has been the subject of investigative effort, speculation, and controversy. The current paradigm assumes that FV activation is initiated by limited proteolysis by traces of (meizo) thrombin. METHODS AND RESULTS—Recombinant tick salivary protein TIX-5 was produced and anticoagulant properties were studied with the use of plasma, whole blood, and purified systems. Here, we report that TIX-5 specifically inhibits FXa-mediated FV activation involving the B domain of FV and show that FXa activation of FV is pivotal for plasma and blood clotting. Accordingly, tick feeding is impaired on TIX-5 immune rabbits, displaying the in vivo importance of TIX-5. CONCLUSIONS—Our data elucidate a unique molecular mechanism by which ticks inhibit the host’s coagulation system. From our data, we propose a revised blood coagulation scheme in which direct FXa-mediated FV activation occurs in the initiation phase during which thrombin-mediated FV activation is restrained by fibrinogen and inhibitors.